A critical analysis on remote collaboration mediated by Augmented Reality: Making a case for improved characterization and evaluation of the collaborative process. (February 2022) - Marques, Bernardo; Teixeira, António; Silva, Samuel; Alves, João; Dias, Paulo; Santos, Beatriz Sousa
Abstract: Remote Collaboration mediated by Mixed and Augmented Reality (MR/AR) shows great potential in scenarios where physically distributed collaborators need to establish a common ground to achieve a shared goal. So far, most research efforts have been devoted to creating the enabling technology, overcoming engineering hurdles and proposing methods to support its design and development. To contribute to more in-depth knowledge on how remote collaboration occurs through these technologies, it is paramount to understand where the field stands and how characterization and evaluation have been conducted. In this vein, this work reports the results of a literature review which shows that evaluation is frequently performed in ad-hoc manners, i.e., disregarding adapting the evaluation methods to collaborative AR. Most studies rely on single-user methods, which are not suitable for collaborative solutions, falling short of retrieving the necessary amount of contextualized data for more comprehensive evaluations. This suggests minimal support of existing frameworks and a lack of theories and guidelines to guide the characterization of the collaborative process using AR. Then, a critical analysis is presented in which we discuss the maturity of the field and a roadmap of important research actions is proposed, that may help address how to improve the characterization and evaluation of the collaboration process moving forward and, in consequence, improve MR/AR based remote collaboration. Graphical abstract: Highlights: How evaluation of the collaborative process is conducted in remote scenarios using AR. Integration of characterization and evaluation methods is of paramount importance. Critical analysis to discuss the maturity of remote collaboration using AR. AR remote collaboration is in the Replication-Empiricism phases of the BRETAM model. Roadmap of research actions to elicit characterization of the collaboration process.